Sensory primary cilium is a responsive cAMP microdomain in renal epithelia - Sherpa, Rinzhin T. (Sci Rep, 2019)
Primary cilia are hair-like cellular extensions that sense microenvironmental signals surrounding cells. The role of adenylyl cyclases in ciliary function has been of interest because the product of adenylyl cyclase activity, cAMP, is relevant to cilia-related diseases. In the present study, we show that vasopressin receptor type-2 (V2R) is localized to cilia in kidney epithelial cells. Pharmacologic inhibition of V2R with tolvaptan increases ciliary length and mechanosensory function. Genetic knockdown of V2R, however, does not have any effect on ciliary length, although the effect of tolvaptan on ciliary length is dampened. Our study reveals that tolvaptan may have a cilia-specific effect independent of V2R or verapamil-sensitive calcium channels. Live-imaging of single cilia shows that V2R activation increases cilioplasmic and cytoplasmic cAMP levels, whereas tolvaptan mediates cAMP changes only in a cilia-specific manner. Furthermore, fluid-shear stress decreases cilioplasmic, but not cytoplasmic cAMP levels. Our data indicate that cilioplasmic and cytoplasmic cAMP levels are differentially modulated. We propose that the cilium is a critical sensor acting as a responsive cAMP microcompartment during physiologically relevant stimuli.